2007
DOI: 10.1021/bi701386f
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Sequence Effects on NarI-Induced −2 Frameshift Mutagenesis by Dynamic 19F NMR, UV, and CD Spectroscopy

Abstract: The NarI recognition sequence (5'-G1G2CG3CN-3') is the most vulnerable hot spot for frameshift mutagenesis induced by the carcinogen 2-aminofluorene and its analogues in Escherichia coli. Lesioning of the guanine in the G3 position induces an especially high frequency of -2 deletion mutations; vulnerability to these mutations is modulated by the nature of the nucleotide in the N position (C approximately A > G > T). The objective of the present study was to probe the structural basis of this N-mediated influen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
95
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 34 publications
(103 citation statements)
references
References 46 publications
7
95
1
Order By: Relevance
“…We have also accumulated an extensive collection of 19 F NMR spectra of fluorinated aminofluorene-modified duplexes in various sequence settings and found that in the base-displaced stacked (S) conformer fluorine is always shielded (upfield) relative to that of the external binding B-type conformer. 14, 15, 26, 29, 44, 48, 4919 F shielding is a hallmark for the van der Waals interaction and the ring current effect caused by the carcinogen moiety within the stacked and bulge duplexes (S-type conformation). 44 We have used a similar strategy to assign the signals in the 19 F NMR spectra of deletion duplexes, i.e., the signals (~ −115 ppm) near the coalescence temperatures arise from denatured single stranded modified exposed fluorine and non-stacked external B-type conformers, and shielded signals arise from a buried fluorinated carcinogen with excess van der Waals interactions with neighboring base pairs as occurs in S-type conformations.…”
Section: Resultsmentioning
confidence: 99%
“…We have also accumulated an extensive collection of 19 F NMR spectra of fluorinated aminofluorene-modified duplexes in various sequence settings and found that in the base-displaced stacked (S) conformer fluorine is always shielded (upfield) relative to that of the external binding B-type conformer. 14, 15, 26, 29, 44, 48, 4919 F shielding is a hallmark for the van der Waals interaction and the ring current effect caused by the carcinogen moiety within the stacked and bulge duplexes (S-type conformation). 44 We have used a similar strategy to assign the signals in the 19 F NMR spectra of deletion duplexes, i.e., the signals (~ −115 ppm) near the coalescence temperatures arise from denatured single stranded modified exposed fluorine and non-stacked external B-type conformers, and shielded signals arise from a buried fluorinated carcinogen with excess van der Waals interactions with neighboring base pairs as occurs in S-type conformations.…”
Section: Resultsmentioning
confidence: 99%
“…This trend is not surprising since base stacking interactions are one of the most important factors that contribute towards the thermal and thermodynamic stability of the DNA duplexes. 17, 18 …”
Section: Discussionmentioning
confidence: 99%
“…14 We also have documented that the incorporation of fluorine atom at the longest axis does not affect the overall conformational and thermodynamic profiles of aminofluorene-modified duplexes (e.g., dG-FAF, dG-FAAF). 17, 30 FAAF-modified 16-mer di-adduct oligodeoxynucleotides were prepared similarly with a longer reaction time (Figure S1, Supporting Information). 14, 15, 31 Experimental details of FAAF modification and HPLC purification are provided in the Supporting Information.…”
Section: Methodsmentioning
confidence: 99%
“…UV-Melting (Cary100 Bio, Beckman) and Circular Dichroism (CD) (J-810, Jasco) experiments were performed using the previously reported procedures (7,20,23,26). …”
Section: Methodsmentioning
confidence: 99%